The effectiveness of group games activities to develop some social skills (communicating – sharing with others – socializing) that aim to reduce abusive behavior with 5 year-old children (an experimental study in Jableh city) - ريا, منال (Latakia University Journal -Medical Sciences Series, 2021)
the purpose of the survey is to verify the effectiveness of a schedule based on group games which develop some social skills (communicating – sharing with others – socializing) that aim to reduce abusive behavior with 5 year-old children. The approach of this survey is semi-experimental. It was conducted on a group of children who show abusive behavior at a Kindergarten (Al Olamaa Al Sighar) in Jableh city. The group was chosen on purpose with ten children. The meters used were social skills scale, abusive behavior scale and a schedule of group games activities (made by the researcher). The results showed that it had positive effects in developing some social skills (communicating – sharing with others – socializing) to reduce abusive behavior with the targeted group.